The religious condition of Ireland, 1770-1850 - Yates, Nigel (Oxford University Press, 2006)
Nigel Yates provides a reassessment of the religious state of Ireland between 1770 and 1850. He argues that this was both a period of intense reform across all the major religious groups in Ireland and also one in which the seeds of religious tension were sown